Effectiveness of the forced usage of alternative digital platforms during the COVID-19 pandemic in project communication management - Sigal Kordova; Ron S. Hirschprung (Heliyon, 2023)
The COVID-19 pandemic social distancing forced a shift from Face-to-Face (F2F) to virtual work sessions, applying innovative digital tools. These tools have previously been neglected, mainly due to a conservative approach or prioritization. Consequently, their effectiveness was never tested in depth. While applying these innovative digital tools during the COVID-19 pandemic was clearly preferable to shutting down organizational activity, managers and workers recognized the advantages of these alternatives and tended to apply them in the post-COVID-19 period. However, in this post-pandemic period, which is free from social distancing limitations, a relatively full space of choices was introduced again, which raised the question whether these alternatives should be kept. Therefore, this study examines whether digital communication tools can adequately substitute F2F sessions in project management. We conducted an experiment with participants (n=269),askingthem to perform project-oriented tasks on four platforms: as individuals, in an F2F group meeting, on Zoom, or using WhatsApp. The results indicate that while an F2F meeting is more effective than individual work, Zoom and WhatsApp are not. These findings appear surprising and may contradict the concept of group empowerment. The use of digital sharing platforms did not affect the tasks’ performances nor create synergy. This raises the issue of whether these digital means are here to stay, should be discarded, or must be upgraded.